2019
DOI: 10.3233/blc-190236
|View full text |Cite
|
Sign up to set email alerts
|

CIS of the Bladder: Significance and Implications for Therapy

Abstract: Purpose of the review: To review the most recent literature with regards to the pathogenesis, diagnostics, clinical implications and treatment strategies for Carcinoma in Situ (CIS) of the Bladder. Recent findings: There have been advancements in understanding the genetic composition and biochemical behavior of CIS. Technological advancements including Photodynamic Diagnosis (PDD) with Hexaminolevulinate (HVA) better detect CIS compared to traditional white light (WL) cystoscopy. Recently published single and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…21 If untreated, 50% of CIS progresses to muscleinvasive disease within 5 years and, even with treatment, 30% to 40% progresses within 10 years. 22 Pembrolizumab is a PD-1 inhibitor that has been evaluated as treatment for BCG-unresponsive NMIBC with CIS in the single-arm, phase II KEYNOTE-057 study (pembrolizumab is also indicated for treatment of metastatic urothelial carcinoma, as described later). In the KEYNOTE-057 study, 101 patients who received previous BCG therapy and were either unable or unwilling to undergo cystectomy were treated with pembrolizumab 23 ; 96 patients were eligible for inclusion in the efficacy analysis.…”
Section: Treatment Of High-risk Nmibcmentioning
confidence: 99%
“…21 If untreated, 50% of CIS progresses to muscleinvasive disease within 5 years and, even with treatment, 30% to 40% progresses within 10 years. 22 Pembrolizumab is a PD-1 inhibitor that has been evaluated as treatment for BCG-unresponsive NMIBC with CIS in the single-arm, phase II KEYNOTE-057 study (pembrolizumab is also indicated for treatment of metastatic urothelial carcinoma, as described later). In the KEYNOTE-057 study, 101 patients who received previous BCG therapy and were either unable or unwilling to undergo cystectomy were treated with pembrolizumab 23 ; 96 patients were eligible for inclusion in the efficacy analysis.…”
Section: Treatment Of High-risk Nmibcmentioning
confidence: 99%
“…For example, early-stage bladder tumors have small papillary structures or appear as a velvety patch on the bladder wall. 25 Under a quick glance, these small tumors may be missed due to the lack of contrast in WLC or distracting inflammation in larger regions of the bladder. However, distinct texture features (such as the velvety, carpet-like mucosa) and small changes in tissue color that are not apparent to human eyes are detectable by the machine learning model.…”
Section: Introductionmentioning
confidence: 99%